Development of Palladium Surface‐Enriched Heteronuclear Au–Pd Nanoparticle Dehalogenation Catalysts in an Ionic Liquid. Issue 4 (4th January 2013) - Yuan, Xiao; Sun, Geng; Asakura, Hiroyuki; Tanaka, Tsunehiro; Chen, Xi; Yuan, Yuan; Laurenczy, Gabor; Kou, Yuan; Dyson, Paul J.; Yan, Ning
Abstract Heteronuclear Au–Pd nanoparticles were prepared and immobilized in the functionalized ionic liquid [C2OHmim][NTf2]. The structural and electronic properties of the nanoparticles were characterized by a range of techniques and the surface of the nanoparticles was found to be enriched in Pd. Moreover, the extent of Pd enrichment is easily controlled by varying the ratio of Au and Pd salts used in the synthesis. The heteronuclear nanoparticles were found to be effective catalysts in dehalogenation reactions with no activity observed for the pure Au nanoparticles and only limited activity for the pure Pd nanoparticles. The activity of the heteronuclear nanoparticles may be attributed to charge transfer from Pd to Au and consequently to more efficient reductive elimination.